Transition scenarios : China and the United States in the twenty-first century - Rapkin, David P.; Thompson, William R. (University of Chicago Press, 2013)
China's rising status in the global economy alongside recent economic stagnation in Europe and the United States has led to considerable speculation that we are in the early stages of a transition in power relations. Commentators have tended to treat this transitional period as a novelty, but history is in fact replete with such systemic transitions-sometimes with perilous results. Can we predict the future by using the past? And, if so, what might history teach us?With Transition Scenarios, David P. Rapkin and William R. Thompson identify some predictors for pow.